2016
DOI: 10.1371/journal.pone.0166935
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Interactions of Human Primary Amine Oxidase with the V and C22 Domains of Sialic Acid-Binding Immunoglobulin-Like Lectin-9 Regulate Its Binding and Amine Oxidase Activity

Abstract: Sialic acid-binding immunoglobulin-like lectin-9 (Siglec-9) on leukocyte surface is a counter-receptor for endothelial cell surface adhesin, human primary amine oxidase (hAOC3), a target protein for anti-inflammatory agents. This interaction can be used to detect inflammation and cancer in vivo, since the labeled peptides derived from the second C2 domain (C22) of Siglec-9 specifically bind to the inflammation-inducible hAOC3. As limited knowledge on the interaction between Siglec-9 and hAOC3 has hampered both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 51 publications
3
15
0
Order By: Relevance
“…The lower Ki for theobromine relative to caffeine may be due to the formation of hydrogen bonds between the nitrogen in position 1 and amino acid side chains on PrAO. Imidazole was reported to be an inhibitor of PrAO at high concentrations (Elovaara et al, ) but at the highest level used herein (1.0 mM) showed only mild inhibition (Figure ).…”
Section: Discussionmentioning
confidence: 72%
“…The lower Ki for theobromine relative to caffeine may be due to the formation of hydrogen bonds between the nitrogen in position 1 and amino acid side chains on PrAO. Imidazole was reported to be an inhibitor of PrAO at high concentrations (Elovaara et al, ) but at the highest level used herein (1.0 mM) showed only mild inhibition (Figure ).…”
Section: Discussionmentioning
confidence: 72%
“…Such an explanation might also account for the complex kinetics observed. As with the bovine enzyme, it is possible that the methylxanthines in this study were binding to one or more imidazole binding site(s) identified in structural studies [40,45]. If blocking both of these binding sites caused inhibition of activity, then the complex kinetics we observed might be expected.…”
Section: Nature Of the Prao Inhibition Induced By Methylxanthines In mentioning
confidence: 82%
“…Moreover, Siglec-9 peptides targeted to hAOC3 have been used for PET (Positron Emission Tomography) imaging of inflammation and cancer using different animal models 9 – 12 and it was originally proposed that the Siglec-9 peptide binds covalently to the TPQ cofactor of hAOC3 8 . According to the recent data obtained using the full Siglec-9 extracellular domain, Siglec-9 is neither a substrate nor inhibitor for hAOC3 but it enhances the catalytic activity of hAOC3 towards the monoamine substrate benzylamine 13 . The interactions between Siglec-9 and the enzymatic groove of hAOC3 are mediated by two arginines located at the C2 2 domain of Siglec-9, Arg284 and Arg290 (R3 and R9 in the peptide, respectively) 8 , 13 .…”
Section: Introductionmentioning
confidence: 99%